Interactional Patterns in Synchronous Online Teaching Mode at the Third Semester of English Education Study Program of University of Bengkulu - Hesty Prastiningrum; Azwandi Azwandi; Gita Mutiara Hati (Journal of English Education and Teaching, 2022)
This research is aimed at finding out the interactional patterns in the synchronous online teaching mode in the third semester of the English Department at the University of Bengkulu. This research employed descriptive quantitative research. The subjects of this research were class C of the third semester of the English Department consisting of 36 students and one lecturer who teaching online by using Google Meet as the synchronous platform. The data of this research were three audiovisual records which were recorded by the lecturer. The data were identified by using the identification table of IRF pattern of interaction based on Coulthard (2002) and analyzed based on the IRF model of Sinclair and Coulthard (1975) as the ideal pattern. The first finding showed that the most occurred pattern employed by the lecturer is IRF pattern as a complete pattern, and there are also IR patterns as a semi-complete pattern, and IF as an incomplete pattern. The second finding showed that the elicitation act is the most frequently occurred act in the classroom interaction. It could be concluded this classroom can be stated as a good interaction because the lecturer gave the same opportunities to the students to initiate the discussion, so the students were active in giving initiations.